ARFI elastography as a complementary diagnostic method for mammary neoplasia in female dogs - preliminary results - Feliciano, M. A. R. [UNESP]; Maronezi, M. C. [UNESP]; Pavan, L. [UNESP]; Castanheira, T. L. [UNESP]; Simoes, A. P. R. [UNESP]; Carvalho, C. F.; Canola, J. C. [UNESP]; Vicente, W. R. R. [UNESP] (Wiley-Blackwell, 2014)
OBJECTIVES: To evaluate the applicability of acoustic radiation force impulse elastography as a complementary method in diagnosing mammary neoplasia in dogs. METHODS: Mammary tumours from 50 female dogs were evaluated and divided into two groups: G1 (benign tissue) and G2 (malignant tumours). The nodules were assessed by B-Mode ultrasonography, qualitative and quantitative acoustic radiation force impulse elastography and histopathology. RESULTS: B-Mode ultrasound examination was ineffective at separating the tumours into the two groups. Likewise, there was no correlation between the grayscale images of the mammary tissue by qualitative elastography. A difference was found in the deformity of the mammary masses between the malignant and benign groups (P=0.002). Using quantitative elastography, the mean values of shear velocity were 3.33 m/s for malignant tumours and 1.28 m/s for benign tissue (P<0.0001). CLINICAL SIGNIFICANCE: The use of acoustic radiation force impulse elastography may help to differentiate between malignant and benign mammary neoplasms.